Paper Chemistry: François Dagognet and the Chemical Graph. (2nd January 2018) - Hepler-Smith, Evan
Abstract : In two books published in 1969 and 1973, the philosopher François Dagognet articulated a sharp contrast between the verbal and the visual in the history of chemical representation. Ursula Klein took up Dagognet's argument as both inspiration and foil in her account of Berzelian formulas as productive "paper tools." Building on Klein's work, I show how Dagognet portrayed chemical names and formulas not just as representations and paper tools, but as material abstractions that were objects of inquiry in themselves. Dagognet associated this way of doing chemistry with chemists' use of computers, citing the work of the physical organic chemist Jacques-Émile Dubois. However, I show that chemical editors and mathematicians had begun to treat chemical names and formulas in this way long before anyone used computers for such studies. Indeed, some of the techniques of graph theory central to the application of computers to chemistry in the mid-twentieth century were themselves in part derived half a century earlier from the application of chemical formulas to mathematical reasoning.